Effect of ATP and 2-oxoglutarate on the in vitro interaction between the NifA GAF domain and the GlnB protein of Azospirillum brasilense - P. Sotomaior; L.M. Araújo; C.Y. Nishikawa; L.F. Huergo; R.A. Monteiro; F.O. Pedrosa; L.S. Chubatsu; E.M. Souza (Brazilian Journal of Medical and Biological Research, 2012)
Azospirillum brasilense is a diazotroph that associates with important agricultural crops and thus has potential to be a nitrogen biofertilizer. The A. brasilense transcription regulator NifA, which seems to be constitutively expressed, activates the transcription of nitrogen fixation genes. It has been suggested that the nitrogen status-signaling protein GlnB regulates NifA activity by direct interaction with the NifA N-terminal GAF domain, preventing the inhibitory effect of this domain under conditions of nitrogen fixation. In the present study, we show that an N-terminal truncated form of NifA no longer required GlnB for activity and lost regulation by ammonium. On the other hand, in trans co-expression of the N-terminal GAF domain inhibited the N-truncated protein in response to fixed nitrogen levels. We also used pull-down assays to show in vitro interaction between the purified N-terminal GAF domain of NifA and the GlnB protein. The results showed that A. brasilense GlnB interacts directly with the NifA N-terminal domain and this interaction is dependent on the presence of ATP and 2-oxoglutarate.